The Modal Age of Statistics. (13th January 2020) - Chacón, José E.
Summary: Recently, a number of statistical problems have found an unexpected solution by inspecting them through a 'modal point of view'. These include classical tasks such as clustering or regression. This has led to a renewed interest in estimation and inference for the mode. This paper offers an extensive survey of the traditional approaches to mode estimation and explores the consequences of applying this modern modal methodology to other, seemingly unrelated, fields.